2021
DOI: 10.1002/anie.202101804
|View full text |Cite
|
Sign up to set email alerts
|

Selective Electrocatalytic Reduction of Oxygen to Hydroxyl Radicals via 3‐Electron Pathway with FeCo Alloy Encapsulated Carbon Aerogel for Fast and Complete Removing Pollutants

Abstract: We reported the selective electrochemical reduction of oxygen (O 2 )t oh ydroxylr adicals (COH) via 3-electron pathway with FeCo alloye ncapsulated by carbon aerogel (FeCoC). The graphite shell with exposed -COOH is conducive to the 2-electron reduction pathway for H 2 O 2 generation stepped by 1-electron reduction towardst oCOH. The electrocatalytic activity can be regulated by tuning the local electronic environment of carbon shell with the electrons coming from the inner FeCo alloy. The new strategy of COH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(86 citation statements)
references
References 64 publications
(1 reference statement)
0
81
0
Order By: Relevance
“…This sharp increase in the value of Rct i indicated that the thickened rGO layer of rGO@Fe x P/C greatly hindered the electron penetration from Fe x P/C to the outer surface of rGO layer. Recent study [ 42 ] has demonstrated the concept that electron penetration from active metal core to carbon layer could stimulate the carbon layer in a variety of catalytic reactions, including the heterogenous EF reaction as Equation (4) shown. The intriguing affecting law of rGO layer thickness on the electrocatalytic activities of rGO@Fe x P/C could further support the concept that carbon shell could be enriched with electron from inner metal cores to electrocatalytic decompose H 2 O 2 into ·OH.…”
Section: Resultsmentioning
confidence: 99%
“…This sharp increase in the value of Rct i indicated that the thickened rGO layer of rGO@Fe x P/C greatly hindered the electron penetration from Fe x P/C to the outer surface of rGO layer. Recent study [ 42 ] has demonstrated the concept that electron penetration from active metal core to carbon layer could stimulate the carbon layer in a variety of catalytic reactions, including the heterogenous EF reaction as Equation (4) shown. The intriguing affecting law of rGO layer thickness on the electrocatalytic activities of rGO@Fe x P/C could further support the concept that carbon shell could be enriched with electron from inner metal cores to electrocatalytic decompose H 2 O 2 into ·OH.…”
Section: Resultsmentioning
confidence: 99%
“…The potential catalytic reduction activity of M‐SACs to different oxidants (PMS, O 2 , and H 2 O 2 ) was further evaluated by electrochemical reduction polarization curves [16] . As shown in Figure 3 i, Figure S18,S19, and Table S8,S9, the specific activities of M‐SACs for catalyzing different oxidants are calculated and verified by the TOF values.…”
Section: Resultsmentioning
confidence: 93%
“…As one of the most efficient AOPs, the PMS‐assisted catalytic production of ROS via transition metal compounds has gained considerable interest [9, 11–13] . Despite abundant transition metal‐based catalysts have already been developed and used in PMS‐assisted AOPs, [14–17] obvious drawbacks such as the fast release of metal ions, slow catalytic kinetics, low atomic utilization rates, and unclear catalytic mechanisms have also been noticed.…”
Section: Introductionmentioning
confidence: 99%
“…The transformation of molecular oxygen to ˙OH and rapid removal of antibiotic ciprofloxacin could be achieved using the integrated iron–cobalt–carbon aerogel cathode with carbon-coated alloy. 112 A laser-induced graphene electrode with higher conductivity produced more H 2 O 2 during the reaction. 95% of Cr( vi ) was removed, and 50% of iohexol was degraded.…”
Section: Pretreatment Methods Of Impurities In Electroplating Wastewatermentioning
confidence: 99%